The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/pc.25145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of POSS fillers on the transport properties of natural rubber nanocomposites

Abstract: Three types of polyhedral oligomeric silsesquioxane (POSS)—octaphenyl (OP), POSS@TESPT (TT), and MWCNT@POSS (VC)—were incorporated into natural rubber (NR) to fabricate nanocomposites. The transport properties of POSS–NR nanocomposites were studied through solvent diffusion techniques. Diffusion studies were done with toluene (aromatic solvent) and the influence of nanofiller structure, concentration and compatibility with the NR matrix on various diffusion parameters were analyzed. The fillers that have good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…As the nano‐HA content increases, the blend matrix becomes more rigid due to the increased degree of reinforcement of the nanoparticles. Therefore, the rate of polymer blend chain relaxation becomes slow compared to the concurrent penetrant diffusion and the transport in filled system follow a relaxation‐controlled diffusion process 41 . As usual, the k values in the reinforced composite system are lower than the neat rubber blend due to the reduced solvent‐matrix interactions, which can be attributed to better 'across phase' adhesion through the improved interface.…”
Section: Resultsmentioning
confidence: 99%
“…As the nano‐HA content increases, the blend matrix becomes more rigid due to the increased degree of reinforcement of the nanoparticles. Therefore, the rate of polymer blend chain relaxation becomes slow compared to the concurrent penetrant diffusion and the transport in filled system follow a relaxation‐controlled diffusion process 41 . As usual, the k values in the reinforced composite system are lower than the neat rubber blend due to the reduced solvent‐matrix interactions, which can be attributed to better 'across phase' adhesion through the improved interface.…”
Section: Resultsmentioning
confidence: 99%
“…They have concluded that equilibrium solvent uptake decreases with increase of CB content due to reduction in free volume 20 . Influence of POSS fillers on transport characteristics of NR was determined by Priya et al 21 wherein fillers with good interaction in polymer matrix showed lowest solvent uptake, which supports studies reported by Maria et al Aminabhavi et al studied the effect of organic liquids on Polyurethane (PU), Chloroprene (CR), NR, NBR, SBR, and ethylene propylene diene rubber. They reported dependency of diffusion parameters on the choice of a solvent molecule and chemical structure of the polymer membrane 22–25 .…”
Section: Introductionmentioning
confidence: 56%
“…One may observe that “k” value for 50phr CB filled rubber vulcanizates decreases in comparison to neat rubber vulcanizates. As the concentration of CB in 70NR/30BR increases, the “k” values shows a decreasing trend for interaction with benzene and toluene but varies when xylene is used as solvent 21 …”
Section: Resultsmentioning
confidence: 99%
“…Polyhedral oligomeric silsesquioxane (POSS), a special type of crystalline silsesquioxane with regular cage-like structures, is often applied as a nanofiller for polymer materials, aiming to improve their mechanical, thermal, and fire retardancy properties. [1][2][3][4][5][6][7] However, though various POSS are commercially available, the cost of POSS remains quite high (one or several US dollar[s] per gram). This highly restricts their real-world applications as nanofillers for commodity polymers, such as polyolefin.…”
Section: Introductionmentioning
confidence: 99%